Pulling out the Most Colourful Threads: Revealing and Weaving Positionality into Collaborative Life Writing. Issue 1 (2nd January 2023) - Piper, Alana; Driscoll, Samadhi
ABSTRACT: This article uses a collaboration between an academic historian and a family historian as a case study for the importance of acknowledging the role of authorial subjectivity within biographical life writing. In particular, it considers the different lenses – from feminist to familial – that can be used to view the rags-to-riches tale of Sydney fortune-teller Mary Scales (1863–1928). By foregrounding our own positionality towards the subject matter our hope is not to avoid subjectivity, but rather expose its influence in shaping our readings of the historical sources through which Mary's life can be (partially) known.